APPLICATION OF GREEN ACCOUNTING AS A STRATEGY TO IMPROVE PROFITABILITY IN BLACK PEARL CHARCOAL MSMES - Dini Ariani; Nurul Inayah; Yenni Samri Juliati Nasution (Pena Cendekia Insani, 2025)
This study aims to examine the implementation of green accounting as a strategy to increase profitability in Arang Mutiara Hitam, a micro-enterprise engaged in coconut shell charcoal production. The research uses a descriptive qualitative method with data collected through interviews, observation, and documentation. The findings indicate that the business owner has practiced environmental and social responsibility by providing compensation to surrounding communities, yet environmental costs have not been systematically recorded in financial reports. As a result, recurring environmental expenditures are not identified as factors affecting business profit, making it difficult for the owner to conduct comprehensive financial evaluations. These findings highlight the importance of green accounting to improve transparency, cost efficiency, and long-term profitability. The study also supports existing theories and prior research asserting that environmental accounting promotes sustainability and strengthens the financial performance of micro-enterprises.